From Reactive to Proactive: AI-Driven CCaaS Solutions in Predictive Customer Service - Vipin Kalra,; Dr Shaveta Arora, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Customer service is no longer the answer to a complaint but a personal, accurate, timely interaction that is expected to be highly influenced by AI. AI is being integrated into CCaaS solutions as more and more of these platforms aim to provide better ways to engage with customers while anticipating their needs and even providing personalized updates. The role of advanced intelligent CCaaS solutions in the context of predictive customer experience transformation is the focus of this paper. These areas are: shift from traditional reactive systems to proactive AI, use of Predictive Analytics, Machine Learning Models and Conversational AI for customer satisfaction. In so doing, this article outlines a comprehensive approach to a literature review and case study analyses to stress the significance of embedding AI into CCaaS for long-term competitive advantage. It calls for the adoption of predictive customer service as critical to organizations that are determined to strive in the current volatile business environment.
Keywords: AI; CCaaS; Predictive Analytics; Customer Service; Machine Learning; Conversational AI; Customer Satisfaction